2012
DOI: 10.1016/j.ultsonch.2011.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Process optimization and stability of d-limonene-in-water nanoemulsions prepared by ultrasonic emulsification using response surface methodology

Abstract: D-limonene in water nanoemulsion was prepared by ultrasonic emulsification using mixed surfactants of sorbitane trioleate and polyoxyethylene (20) oleyl ether. Investigation using response surface methodology revealed that 10% d-limonene nanoemulsions formed at S0 ratio (D-limonene concentration to mixed surfactant concentration) 0.6-0.7 and applied power 18 W for 120 s had droplet size below 100 nm. The zeta potential of the nanoemulsion was approximately -20 mV at original pH 6.4, closed to zero around pH 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
147
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(165 citation statements)
references
References 28 publications
9
147
0
9
Order By: Relevance
“…For emulsification by lowenergy methods, composition variables have much higher influence than preparation variables. 64 Our results agreed with other studies, 58,60 which showed that increased water fraction resulted in an increase in particle sizes.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…For emulsification by lowenergy methods, composition variables have much higher influence than preparation variables. 64 Our results agreed with other studies, 58,60 which showed that increased water fraction resulted in an increase in particle sizes.…”
supporting
confidence: 92%
“…22 Surfactant concentration controls the total surface area of the droplets, rate of droplet dispersion, and coalescence. 58 The concentration of glycerol increases, affecting the properties of TW80 and forcing the glycerol to penetrate the interfacial region, accounting for the observed decrease in droplet size and particle-size distribution.…”
Section: Glycerol Weight Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Limonene is widely used in food and cosmetic industries, and also in production of refrigerant fluids, paints, agrochemicals and cleaning agents. [8][9][10][11][12][13] R-(+)-limonene is the major component (about 97%) of the orange oil obtained from orange and lemon peels (biomass) which are the waste product of the citrus fruit industry. The main methods of obtaining orange oil from the orange peels are: cold pressing and distillation.…”
Section: Introductionmentioning
confidence: 99%
“…The droplet size and size distribution of nanoemulsion was also characterized. Hence, instead of using high energy sonication and microfluidization of d-limonene to form nanoemulsion 17 , stable d-limonene nanoemulsion was prepared by the addition of an optimum microemulsion composition directly into water by gentle mixing at room temperature. The studies provide guidance to prepare d-limonene nanoemulsion system by low energy for practical applications.…”
Section: Introductionmentioning
confidence: 99%